Knowledge, attitudes, and practices of breastfeeding among women visiting primary healthcare clinics on the island of Abu Dhabi, United Arab Emirates - Mai Isam Al Ketbi; Sultan Al Noman; Abdelqadir Al Ali; Ebtihal Darwish; Maha Al Fahim; Jaishen Rajah (BMC, 2018)
Abstract Background The World Health Organization recommends continued breastfeeding up to 2 years of age or beyond. This study assessed breastfeeding knowledge, attitudes, and practices among women residing on the island of Abu Dhabi and identified associated factors. Methods We conducted a cross-sectional study using a self-administered questionnaire among mothers visiting primary healthcare clinics in Abu Dhabi between November 2014 and 2015. Participants were women aged at least 18 years who had at least one child aged 2 years or younger at the time of the study. Breastfeeding knowledge, attitudes, and practices were assessed on the basis of experience with last child. Selected questions were used to develop a scaled scoring system to categorize these aspects as good, fair, or poor. Exclusive breastfeeding is defined as the act of feeding infants only breast milk since birth, without providing water, formula, or other liquid supplements. Results The participants were 344 women. Exclusive breastfeeding for 6 months was reported by only 46 (16.9%, 95% CI 0.10, 0.17, n = 272). 79 (28.7%, n = 275) of the participants were breastfeeding and planning to continue after the child was ≥24 months. Multivariate logistic regression analysis revealed that the following factors were associated with exclusive breastfeeding: mothers with female children (adjusted OR [AOR] 2.42; 95% CI 1.18, 4.97) and better breastfeeding knowledge scores (AOR 1.25; 95% CI 1.04, 1.50). The following factors were associated with less likelihood of exclusively breastfeeding: working mothers (AOR 0.29; 95% CI 0.12, 0.72), living with relatives (AOR 0.21; 95% CI 0.05, 0.81), no past exclusive breastfeeding experience (AOR 0.23; 95% CI 0.09, 0.58) and being offered readymade liquid formula in hospital (AOR 0.33; 95% CI 0.15, 0.72). The most common reason for stopping breastfeeding was insufficient breast milk production (68/89, 76%), and the most common work related reason was inadequate maternity leave (24/89, 15%). Conclusion Although breastfeeding knowledge was generally good, breastfeeding practice was still suboptimal. Modifiable factors found to predict exclusive breastfeeding included breastfeeding knowledge and mothers' employment status.